2019
DOI: 10.1007/s10745-019-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Buffer Zone Programs to Reduce Human-Wildlife Impacts: the Case of the Chitwan National Park, Nepal

Abstract: Buffer zones around parks/reserves are designed to maintain ecological integrity and to ensure community participation in biodiversity conservation. We studied the fund utilization pattern of buffer zone programs, mitigation measures practiced, and attitudes of residents in buffer zone programs of Chitwan National Park, Nepal. The buffer zone committees spent only a small portion (13.7%) of their budget in direct interventions to reduce wildlife impacts. Human-wildlife conflicts were inversely related to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 31 publications
2
55
0
2
Order By: Relevance
“…In a Ugandan human‐carnivore conflict context further investigations are required into how the communities affected by carnivore depredation could be more involved in the mitigation process. Models such as those in Kenya (e.g., Okello et al, 2014) and Nepal (e.g., Lamichhane et al, 2019) where community members are directly involved in the management and enforcement of financial compensation and intervention scheme rules should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In a Ugandan human‐carnivore conflict context further investigations are required into how the communities affected by carnivore depredation could be more involved in the mitigation process. Models such as those in Kenya (e.g., Okello et al, 2014) and Nepal (e.g., Lamichhane et al, 2019) where community members are directly involved in the management and enforcement of financial compensation and intervention scheme rules should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that these activities have helped to improve the livelihoods of some of the pastoral communities in the study area, in addition to improving rangeland management to some extent. Other studies in Nepal have also reported enhanced livelihoods of buffer zone communities due to: Income diversification, capacity enhancement, resource conservation, ecotourism promotion, increased farm production, and reduced conflict between Park authorities and communities through revenue distribution schemes [43][44][45].…”
Section: National Policy and Institutional Frameworkmentioning
confidence: 92%
“…For a multiple decades, tigers and leopards have co-occurred with a large overlap of home range and diet (Seidensticker 1976). Factors facilitating the high density of these two large cats in Chitwan may be a combination of high density of ungulates (73 prey per km 2 , Dhakal et al 2014), mosaics of the habitats (Bhattarai and Kindlmann 2012a), control of hunting with enhanced protection, habitat restoration in the buffer zone (Gurung et al 2008) and support from local communities (Nepal and Spiteri 2011;Lamichhane et al 2019).…”
Section: Tiger-leopard Densitymentioning
confidence: 99%